(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
The researchers adopted the descriptive approach using the survey method and correlational relationships, as it is appropriate for the nature of the research problem. The research population was selected intentionally, consisting of second-year students at the College of Physical Education and Sports Sciences, University of Kirkuk, for the academic year (2024-2025), totaling (226) students, representing (100%) of the population. The main research sample consisted of (26) students. Based on the data collected and the statistical analyses conducted, the researchers reached the following conclusions